Gardner's chemical synonyms and trade names (Ashgate, 1999)
The main criterion for inclusion in Gardner's is a material's importance as a commercially available chemical. Thus all bulk inorganic chemicals, major pesticides, dyestuffs, surfactants, metals and alloys are included.